Metropolitan Representations of the Colonised Other(s) in the Photographs of the 1907 Campaign of the Cuamato in the South of Angola - Silveira Pereira, Hugo (Eikón / Imago, 2020)
In 1907, a Portuguese military campaign arrived in southern Angola to subdue the local peoples. Among the soldiers, followed two photographers, who recorded different moments of the manoeuvres and various aspects of the landscape and the natives, which were later published in the press. In this article, I analyse these images in the context of the relationship between the European Self and the African Other(s). I show how the images contributed to an unequal power relationship between colonizer and colonized, by solidifying the representation of African primitivism, as an improper condition, which justified the European’s civilizing action.